Data acquisition, processing and filtering for reliable 3D resistivity and time‐domain induced polarisation tomography in an urban area: field example of Vinsta, Stockholm. Issue 3 (1st April 2018) - Rossi, Matteo; Dahlin, Tbrleif; Olsson, Per‐Ivar; Günther, Thomas
ABSTRACT: There is an increasing demand for trustworthy engineering geological conceptual models in urban areas due to an increasing trend in the underground infrastructure construction. Good‐quality site investigations can reduce the risk of encountering unexpected geological conditions during construction. Geoelectrical measurements can be used as a tool for providing an overview of the site conditions and serve as a base for planning a geotechnical drilling program and for integration of the results. Geophysical surveys in urban environments may encounter problems due to strict logistical constraints and may be severely affected by electric and electromagnetic noise. Careful processing of the data is necessary to obtain a reliable estimation of the electrical properties of the ground, both electrical resistivity and chargeability. A large three‐dimensional dataset was acquired in the suburban area of Stockholm (Sweden), with the aim of investigating a weak zone in the crystalline bedrock, which had been pointed out by prior geological and geotechnical surveys. Full waveforms of potential dipoles were recorded and processed for removing harmonic noise and background drift. Moreover, a statistical algorithm for handling the quality of the full‐waveform shapes has been proposed. The goodness‐of‐fit test identifies full waveforms with noise that derives from direct current injections, caused by grounding spots of the adjacent metro line. The processed dataset is inverted for electrical resistivity and integral chargeability. The results image a large three‐dimensional volume of the underground. The inverted distribution of geophysical quantities marks out the presence of a wide zone of weak rock, which was not identified by geotechnical probing in the site investigation but documented during the construction phase. Such zones can potentially cause severe problems during the construction of underground infrastructure.